Consumer protection in the service industry under the Consumer Protection Act 1999 - Abu Bakar, Elistina; Amin, Naemah (Ministry of Domestic Trade, Co-operatives and Consumerism, 2011)
The Consumer Protection Act 1999 (CPA) that came into force on 15 November 1999 represents a milestone in consumer protection in Malaysia.It has several important provisions, some of which are more beneficial than those found in the law of contract and law of tort since its objective is specifically to protect the interest of consumers. The statute is applicable to both goods and services but the provisions on services are very important because previously the laws regulating the supply of services seem to be left behind compared to those regulating goods.The aim of this article is to examine the workings of the CPA and its applications in the service indusrty.The protection available is highlighted and the shortfalls, if any, are examined in the light of consumer protection in Malaysia. The central discussion is on Part VII which provides for four implied guarantees in respect of the supply of services namely,implied guarantee as to resonable care and skill, implied guarantee as to fitness for particular purpose, implied guarantee as to time of completion and implied as to price. By enactment of the CPA, it is hoped that all the shortfalls under the contract laws and the tort laws can be remedied.